Multistarter from organic viticulture for red wine Montepulciano d’Abruzzo production - Suzzi, Giovanna; Schirone, Maria; Sergi, Manuel; Marianella, Rosa Maria; Fasoli, Giuseppe; Aguzzi, Irene; Tofalo, Rosanna (Frontiers in Microbiology, 2012)
In the last years the use of a multistarter fermentation process has been proposed to improve the organoleptic characteristics of wines. In the present study the fermentation performances and the interactions of mixed and sequential cultures of Hanseniasporauvarum, Candida zemplinina, and a strain of Saccharomycescerevisiae isolated from organic musts were investigated. To evaluate the oenological performances of the tested strains microvinifications in pasteurized red grape juice from Montepulciano d’Abruzzo cultivar were compared. The course of fermentation has been controlled through classical determinations (CO2 evolution, ethanol, glycerol, pH, total titratable acidity, sugar content, free sulfur dioxide (SO2), dry extract, sugars, organic acids, and volatile compounds). Moreover, the yeast population was determined by both culture-dependent and independent approaches. In particular, the pure culture of H. uvarum and C. zemplinina did not end the fermentation. On the contrary, when S. cerevisiae was added, fermentations were faster confirming that yeast interactions influence the fermentation kinetics. Moreover, C. zemplinina showed a good interaction with S. cerevisiae by increasing the fermentation kinetic in high gravity Montepulciano must, with low ethyl acetate and acetic acid production. This study confirmed that non-Saccharomyces yeasts play a crucial role also in organic wines and their activity could be modulated through the selection of appropriate strains that correctly interact with S. cerevisiae.